Diagnosis of food-dependent exercise-induced anaphylaxis in a female rower: Level 4 case study - Sedlmayer, V.; Appold, E.; MacKnight, J. M.; Moore, E. M. (International Journal of Athletic Therapy & Training, 2025)
A 19-year-old female collegiate rower with a history of multiple food allergies presented with full-body urticaria after two separate practices, 4 days apart. Patient has a history of anaphylaxis every 2 months and takes allergy medications. No known allergens were identified after food recall. Referred to a medical doctor and allergist, patient underwent a 3-week wheat elimination diet and had no further reactions. Diagnosed with food-dependent exercise-induced anaphylaxis, patient was instructed to avoid gluten and other trigger foods pre- and postexercise, and to carry an epinephrine auto-injector while rowing. Patient made a full return to sport.